2002
DOI: 10.1074/jbc.m204185200
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-2 Acts Upstream of Mitochondria to Promote Cytochromec Release during Etoposide-induced Apoptosis

Abstract: DNA damage induced by the cancer chemotherapeutic drug etoposide triggers the onset of a series of intracellular events characteristic of apoptosis. Among the early changes observed is the release of cytochrome c from mitochondria, although the mechanism responsible for this effect is unclear. We demonstrate here a role for caspase-2 in etoposide-induced cytochrome c release. In particular, Jurkat T-lymphocytes treated with an irreversible caspase-2 inhibitor, benzyloxycarbonylVal-Asp-Val-Ala-Asp-fluoromethyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
325
3
4

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 380 publications
(356 citation statements)
references
References 35 publications
24
325
3
4
Order By: Relevance
“…The latter is possibly due to the activation of caspase 2, which occurs independently of caspase 9 activity in MX781-treated cells and may provoke the translocation of proapoptotic proteins from the mitochondria. 15,16,64 This assumption is further supported by our observations that Z-VAD-fmk, a poor inhibitor of caspase 2, 65 weakly prevented MX781-mediated release of Smac.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The latter is possibly due to the activation of caspase 2, which occurs independently of caspase 9 activity in MX781-treated cells and may provoke the translocation of proapoptotic proteins from the mitochondria. 15,16,64 This assumption is further supported by our observations that Z-VAD-fmk, a poor inhibitor of caspase 2, 65 weakly prevented MX781-mediated release of Smac.…”
Section: Discussionsupporting
confidence: 68%
“…66 Despite the activation of caspase 2 by MX781 in cells overexpressing Bcl-2 or C9DN, this is not sufficient to cause the rapid induction of DEVDase activity that is observed in control cells, in which the mitochondria-caspase 9 loop is functional. No substrates for caspase 2 have been identified, with the exception of golgin p160 67 and, therefore, the consequences of caspase 2 activity other than targeting mitochondria 15,16,64 are not completely understood. The activation of caspase 2 upstream of caspase 9 is perhaps responsible for the degradation of PARP observed in Jurkat-C9DN cells stimulated with MX781, which occurs in the presence of low levels of DEVDase activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested caspase-2 acts upstream of MOMP (Guo et al, 2002;Kumar and Vaux, 2002;Lassus et al, 2002;Paroni et al, 2002;Robertson et al, 2002;Zhivotovsky and Orrenius, 2005). It has been shown to cause MOMP by activating Bid and Bax (Bonzon et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These include Bad, Bax, PUMA and Noxa (for a recent review, see Roos and Kaina, 2006). Furthermore, caspase-2 has been shown to be activated by PIDD and to act upstream of the mitochondria by promoting mitochondrial membrane permeabilization (Guo et al, 2002;Lassus et al, 2002;Robertson et al, 2002). Caspase-2 can act indirectly on the mitochondria by cleaving and activating Bid (Guo et al, 2002) or by directly targeting the mitochondria, independently of its enzymatic activity (Robertson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%